THE EFFECT OF ALPHA-MANGOSTIN ON TRANSFORMING GROWTH FACTOR BETA 1 (TGF-β1) AND MATRIX METALLOPROTEINASE-3 EXPRESSION IN TGF-β-INDUCED HEPATIC STELLATE CELLS - ADENINA, SYARINTA; RAHMANIAH, RAHMANIAH; YUYUNTIA, YUYUNTIA; SOETIKNO, VIVIAN; LOUISA, MELVA (International Journal of Applied Pharmaceutics, 2019)
Objective: Alpha-mangostin (α-MG) has been shown to possess antifibrotic effects. However, the specific mechanism of action of this compound remains poorly understood. Therefore, the aim of this study was to investigate the effect of α-MG on the expression levels of transforming growth factor (TGF)-β1 and matrix metalloproteinase-3 (MMP3) in hepatic stellate cells (HSCs) induced by TGF-β. Methods: Immortalized HSCs and LX-2 cells were incubated with TGF-β with or without α-MG (5 and 10 μM). The viability of LX-2 cells was assessed using the Trypan Blue Exclusion Method. The effect of α-MG on cell morphology and the mRNA expression levels of TGF-β1, TGF-β receptor, and MMP3 was then evaluated. Results: TGF-β enhanced the proliferation of HSCs and caused significant increases in the expression levels of TGF-β1, TGF-β receptor, and MMP3. α-MG treatment reduced the proliferation of HSCs and decreased the expression levels of TGF-β1, TGF-β1 receptor, and MMP3. Conclusion: α-MG is a potential antifibrotic agent due to its antiproliferative and antifibrogenic effects, mainly by suppressing the expression of TGF-β and MMP3 on the surfaces of activated HSCs.